SISTEM PENGUPAHAN DAN PEMBAGIAN KERJA PEREMPUAN BURUH BATIK BERBASIS PUTTING OUT SYSTEM DI KOTA PEKALONGAN (Proses dan Implikasi Marginalisasi Terhadap Perempuan Buruh Batik) - Rita Rahmawati; Shinta Dewi Rismawati; Esti Zaduqisty (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
This research was motivated by the rampant of batik female workers who worked with the Putting Out System (POS) and were marginalized in Pekalongan City. This study was aimed to answer the research questions: what was the marginalization form of women workers through the wage system and division of labor in the production chain based on POS was; the actors who were involved in the process; what factors caused it; and what was implications for women workers, their family and bosses inside production process as well as outside the production process. In-depth interview and observation were used to investigate data. Triangulation of data source and investigating method were also used to validate the investigated data. In addition, Interactive model was used to analyze. The results were: (1) the actors who played a role in the process of marginalization of women workers in Pekalongan batik is the boss, makloon, religious elite (Kyai / Ustazd - ah), and the state; (2) the cause root of that marginalization was manipulated by patriarchal and capitalism ideology; and (3) the implication of that marginalization for woman workers inside production process was that they were positioned as a production machine to make a profit. While the implications outside the production process, they still lived in poverty.